Relation Between HER-2 Gene Expression and Gleason Score in Patients with Prostate Cancer - Mofid, Bahram; Jalali Nodushan, Mohammadreza; Rakhsha, Afshin; Zeinali, Lida; Mirzaei, Hamidreza (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: HER-2 is a proto-oncogene of the tyrosine kinase receptor family on chromosome 17. Overexpression of this gene affects the growth and prognosis of some tumors. This study was performed to evaluate the expression of the HER-2 gene in patients with prostate cancer and its relation with the Gleason score. Materials and Methods: Pathology specimens of all men with prostate cancer who had undergone radical prostatectomy without any supportive treatment were studied. The Gleason scores of the specimens and the expression of HER-2 gene were examined. The expression of HER-2 was scored between zero and 3+ in accordance with the HercepTest method. Patients with scores of 2+ and 3+ were considered to be positive for HER-2 overexpression. Results: Of 150 cancerous prostate specimens evaluated, 20 (13.3%) were positive for HER-2 gene overexpression. A weakly positive HER-2 overexpression (2+) was seen in 15 of them (75%) and the remaining 5 (25%) were strongly positive. The Gleason score was not different between the HER-2-postitive and HER-2-negative patients (P = .08). Fourteen out of 97 patients (14.4%) with a Gleason score less than 7 and 6 out of 53 (11.3%) with scores of 7 or greater were positive for HER-2 overexpression. Conclusion: The frequency of HER-2 gene overexpression is not very high in our patients with prostate cancer, and we failed to show any association of HER-2 expression and the Gleason score.